Периопераційні зміни стану здоров’я пацієнтів з ускладненими формами раку товстого кишківника - Кубрак, Михайло Анатолійович; Завгородній, Сергій Миколайович; Kubrak, M. A.; Zavgorodniy, S. M. (My University, 2023)
Мета. Провести аналіз периопераційних змін стану здоров’я хворих, що були оперовані з приводу ускладнених форм раку товстого кишківника в умовах загальнохірургічного стаціонару з використанням прогностичної шкали CR-POSSUM. Матеріали і методи. Проаналізовано дані 71 (100 %) хворого, які проходили лікування у хірургічному відділенні з приводу ускладнених форм раку товстого кишківника. На доопераційному етапі в першу добу післяопераційного періоду та перед випискою хворого зі стаціонару пацієнтам проводилася оцінка стану здоров’я за шкалою СR-POSSUM. Результати. На етапі госпіталізації середній бал за фізіологічною субшкалою (ФС) склав 10,62 ± 3,04 балів, за хірургічною субшкалою (ХС) – 10,82 ± 2,78 балів. Ризик смертності - 6,40 (3,50; 19,10) %. За результатами повторної оцінки через добу після втручання середній бал за ФС склав 11,73 ± 3,07 балів, Т = 87,00; р ˂ 0,0001. Оцінка за ХС склала 10,81 ± 2,67 балів, Т = 2,00; р = 0,5930. Ризик смертності - 11,60 (4,80; 21,20) %, Т = 55,00; р ˂ 0,0001. Перед випискою середній бал за ФС склав 10,63 ± 2,91 балів, Т = 370,00; р = 0,3082. За ХС бальна оцінка склала 10,74 ± 2,66 балів, Т = 2,00; р = 0,4660. Ризик смертності - 8,10 (3,40; 16,30) %, Т = 345,00; р = 0,2679. The aim of the study. To conduct an analysis of perioperative changes in the state of health of patients who were operated on for complicated forms of colon cancer in the conditions of a general surgical hospi-tal using the CR-POSSUM prognostic scale. Materials and methods. The data of 71 (100%) patients who were treated in the surgical department for complicated forms of colon cancer were analyzed. At the preoperative stage, on the first day of the postoperative pe-riod, and before discharge from the hospital, patients were assessed for their health status using the CR-POSSUM scale. The study group included 36 (50.71%) men and 35 (49.29%) women, whose average age was 67.97 ± 12.71 years. According to the examination results, 49 (69.01%) patients were diagnosed with a colon tumor with acute in-testinal obstruction, 13 (18.31%) with tumor perforation, 3 (4.23%) patients with acute intestinal bleeding, 4 (5.63%) had a combination of acute intestinal obstruction with per-foration of a colon tumor, another 2 (2.82%) had a combi-nation of intestinal obstruction with bleeding. According to the localization, a cecum tumor was diagnosed in 8 (11.27%) patients, ascending colon – in 8 (11.27%), hepatic flexure – in 5 (7.04%) patients, trans-verse colon – in 2 (2 ,82 %), splenic fold - in 1 (1.41 %), descending colon - in 8 (11.27 %), sigmoid - in 30 (42.25 %) operated, rectosigmoid section - in 9 (12, 68%) of pa-tients. All patients were operated on in an average period of 8.2 (5.00; 15.50) hours from the moment of hospitalization.
Perioperative changes in the health condition of patients with complicated forms of colon cancer
Кубрак М. А. - ORCID ID: 0000-0003-4051-9336; Завгородній С. М. - ORCID ID: 0000-0003-3082-3406.
Keywords: рак; товстий кишківник; ускладнення; прогностичні шкали; CR-POSSUM; cancer; colon; complications; prognostic scales